Regulation of Cardiac Contractility by the Alpha 2 Subunit of the Na+/K+-ATPase - Skogestad, Jonas; Aronsen, Jan Magnus (Frontiers in Physiology, 2022)
Cytosolic Na + concentrations regulate cardiac excitation-contraction coupling and contractility. Inhibition of the Na+/K+-ATPase (NKA) activity increases cardiac contractility by increasing cytosolic Ca2+ levels, as increased cytosolic Na+ levels are coupled to less Ca2+ extrusion and/or increased Ca2+ influx from the Na+/Ca2+-exchanger. NKA consists of one α subunit and one β subunit, with α1 and α2 being the main α isoforms in cardiomyocytes. Substantial evidence suggests that NKAα2 is the primary regulator of cardiac contractility despite being outnumbered by NKAα1 in cardiomyocytes. This review will mainly focus on differential regulation and subcellular localization of the NKAα1 and NKAα2 isoforms, and their relation to the proposed concept of subcellular gradients of Na+ in cardiomyocytes. We will also discuss the potential roles of NKAα2 in mediating cardiac hypertrophy and ventricular arrhythmias.